ADOPTION OF CLIMATE-SMART AGRICULTURAL PRACTICES: EMPIRICAL EVIDENCE AMONG VEGETABLE FARMERS IN BASSA, NIGERIA - Godfrey C. Onuwaa; Oludare Adediireb; Cletus Ajomac; Ganiyu Binuyoa (Big Data in Agriculture)
Adoption of climate-smart agricultural practices has several implications and benefits for sustainable agriculture. Therefore, this study analyzed the adoption of climate-smart agricultural practices among vegetable farmers in Bassa, Plateau State, Nigeria. Vegetable farmers were selected using multistage sampling techniques. Primary data collected was analyzed using descriptive statistics, weighted average index and adoption index techniques. The mean age, household size, education (in years), farming experience, farm size were 41 years, 7 people, 7 years, 16 years, and 2ha respectively. Most (88.9%) are male, 82.8% are married, 90.9% had no extension contact; 93.9% have no access to agricultural credit and 92.9% do not belong to any farmer groups or cooperatives. The perceived effects of climate change were indicated by the weighted average index of the following factors: Increased temperature (3.12), irregular rainfall pattern (2.70), incidence of drought (2.37), decline in crop productivity (2.19) and food shortage/insecurity (2.01). Agricultural practices adopted include irrigation facilities (87.8%), improved seed varieties (70.7%), planting mdate adjustments (63.6%), farm diversification (55.5%) and agro-chemical application (51.5%). Most (68.6%) have low adoption index of ≤0.4.The constraints affecting the adoption of climate-smart agricultural mpractices among respondents in the study area include inadequate climate information (89.8%), financial constraints (77.7%), cost of agricultural inputs (65.6%), poor access to extension services (58.5%), farm size/tenure status (51.5%). This study recommends: Improved dissemination and awareness of climate information, financial inclusion, extension contact, land policy modification, adequate input supply at subsidized rates and provision of technical support.